Quality Management of Islamic Education - Budi Ilham Maliki; Heni Susanti; Hani Sobihah; Abdul Mu’in; Anis Fauzi (Formosa Journal of Science and Technology, 2024)
The education quality assurance system in Indonesia, which is regulated in Minister of National Education Regulation Number 63 of 2009, covers many things, including quality limits, quality assurance objectives and quality level references, among others the oldest in several articles. The ultimate goal of ensuring the quality of education is the high intelligence of human life and the nation as envisioned in the Preamble to the Constitution. This study was carried out using a library study method which focused on searching for sources through books, journals and available literature. The approach used in this writing uses a qualitative approach. The aim of this study is to find out how to manage or manage quality in Islamic educational institutions as well as tips for creating and maintaining quality Islamic educational institutions. The research results show that it is in accordance with the concept of quality in education which includes input-process-output elements. So education quality control is also directed at input, process and output aspects. The quality of educational institutions will be realized if all existing systems in educational institutions are oriented towards improving the quality of educational institutions, one way is through the implementation of Total Quality Management (TQM). Through the application of TQM, efforts to build a quality-oriented organizational culture structure can be realized in accordance with the expected competency targets.